PREVALENCE AND DISTRIBUTION OF MICROBIAL CONTAMINATION IN RAW MILK AND PROCESSED DAIRY PRODUCTS IN JOS METROPOLIS - Petlong, C.V.; Zailani, S.A.; Abubakar, A.A.; Salifu, U.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigates the microbial contamination of dairy products collected from four locations within Jos Metropolis; (Tina Junction, Farin Gada, Terminus, and Katako) within Jos Metropolis. A total of 200 dairy samples, including raw milk, Nono (fermented milk): Cheese, and Yoghurt, were aseptically collected and analyzed using standard microbiological methods. The results revealed a significant variation in bacterial prevalence across locations and product types. Bacillus spp. was the most frequently isolated bacterium; it was detected in 144 samples (72.0%): with the highest prevalence in raw milk (94.0%) and nono (92.0%). Mycobacterium bovis (M. bovis) was detected exclusively in raw milk (6.0%): indicating a potential risk of zoonotic transmission through unpasteurized dairy. Processed dairy products had a higher occurrence of yeast cells (13.2%): Micrococcus (2.8%): and Staphylococcus (10.4%): suggesting contamination may have occurred during processing and or storage. Among the sampling locations, Farin Gada and Katako had the highest microbial prevalence of 92.0% and 82.0%, respectively, while Tina Junction and Terminus recorded lower contamination levels (60.0% each). Raw milk had prevalence of 34.7% compared to processed dairy products (94.0%). It was concluded that, raw milk poses a significant risk of microbial contamination, while processed dairy products are susceptible to post-processing contamination. Given the high prevalence of Bacillus spp. (72.0%) and the presence of M. bovis in raw milk, all raw dairy products are recommended to undergo pasteurization or other heat treatments before consumption to eliminate harmful pathogens.